2020
DOI: 10.1371/journal.pone.0237739
|View full text |Cite
|
Sign up to set email alerts
|

Lipids, biomarkers, and subclinical atherosclerosis in treatment-naive HIV patients starting or not starting antiretroviral therapy: Comparison with a healthy control group in a 2-year prospective study

Abstract: Objective To assess the effect of HIV infection and combined antiretroviral therapy (c-ART) on various proatherogenic biomarkers and lipids and to investigate their relationship with subclinical atherosclerosis in a cohort of treatment-naive HIV-infected patients. Methods We performed a prospective, comparative, multicenter study of 2 groups of treatment-naive HIV-infected patients (group A, CD4>500 cells/μL, not starting c-ART; and group B, CD4<500 cells/μL, starting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…This increase was higher than expected for the intraindividual long-term biological variation, which was established in 6% for TC, 7.8% for LDL-c, 19.9% for TG, and 7.3% for HDL-c [32]. These increases may be considered a return of a healthier state in terms of lipids, as previously described in observational studies, and they may be related to decreases in inflammation and immune activation mediated by virological suppression [5,8]. However, when RAL and DTG (no data are available for BIC) were combined with TDF, no changes or even a tendency toward reducing lipid plasma concentrations were found in the trials.…”
Section: Summary Of Studies Comparing Insts In Treatment-naïve Patientsmentioning
confidence: 52%
See 1 more Smart Citation
“…This increase was higher than expected for the intraindividual long-term biological variation, which was established in 6% for TC, 7.8% for LDL-c, 19.9% for TG, and 7.3% for HDL-c [32]. These increases may be considered a return of a healthier state in terms of lipids, as previously described in observational studies, and they may be related to decreases in inflammation and immune activation mediated by virological suppression [5,8]. However, when RAL and DTG (no data are available for BIC) were combined with TDF, no changes or even a tendency toward reducing lipid plasma concentrations were found in the trials.…”
Section: Summary Of Studies Comparing Insts In Treatment-naïve Patientsmentioning
confidence: 52%
“…Non-treated chronic HIV infection, as well as other chronic infections and inflammation conditions, is associated with an atherogenic lipid phenotype. This phenotype is characterized by changes in lipid concentrations, including decreased levels of high-density lipoprotein cholesterol (HDL-c), total cholesterol (TC), and increased levels of triglycerides (TG), as well as modifications in lipid composition and function [5][6][7][8]. The initiation of combined ART has been associated with lipid changes, which can be considered a return to a "healthy" state [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also reported higher CRP levels among individuals with HIV compared to individuals without HIV (21)(22)(23), but higher levels among individuals without HIV have also been observed (24). CRP levels observed in different studies varies remarkedly as it is affected by factors such as nutritional status, ART experience, and other chronic comorbidities or infections (10,21,(23)(24)(25). In the present study the median s-CRP was 2.08 mg/l in individuals with HIV and the CRP concentration increased with disease progression.…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, the median CRP level was higher in individuals with HIV compared to individuals without HIV. Other studies have also reported higher CRP levels among individuals with HIV compared to individuals without HIV (21)(22)(23), but higher levels among individuals without HIV have also been observed (24). CRP levels observed in different studies varies remarkedly as it is affected by factors such as nutritional status, ART experience, and other chronic comorbidities or infections (10,21,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 96%
“…Even though newer antiretrovirals do not elevate circulating lipids to the same extent, tenofovir prodrugs, including tenofovir alafenamide, increase cholesterol species (91). This occurs despite the known impact of HIV on diminishing total cholesterol levels (86,(92)(93)(94)(95). Conversely other ARTs, including raltegravir, dolutegravir, and bictegravir, have either a beneficial or minimal impact on the cholesterol profile after changing regimens from older protease inhibitors (86,96).…”
Section: Discussionmentioning
confidence: 99%